Strategi Pengembangan Organisasi Dalam Menghadapi Revolusi Industri 4.0: Studi Kasus Pimpinan Pusat Ikatan Pelajar Nahdlatul Ulama (PP IPNU) Tahun 2019-2021 - Ma'arif, Nasrul; Runturambi, Arthur Josias Simon (Journal Of Middle East and Islamic Studies, 2022)
The Nahdlatul Ulama Student Association (IPNU) is an autonomous body of the Nahdlatul Ulama (NU) socio-religious organization that carries out the noble mandate as a cadre organization for male students and santri. IPNU is a forum for the struggle of Nahdlatul Ulama students to prepare cadres to succeed Nahdlatul Ulama and national leaders. The Industrial Revolution 4.0 which was marked by technological developments became a challenge for the IPNU Central Management (PP IPNU) to remain consistent in carrying out the mandate and duties of IPNU. This reasearch uses a qualitative approach with descriptive analysis. The researcher uses the System Theory and Action Research Theory to find out the efforts to develop the NU organization in facing the Industrial Revolution 4.0. Based on System Theory, IPNU prioritizes systematic organizational management with the organization's digitalization movement, in the form of SIAPNU and SAM IPNU to support organizational needs such as correspondence and databases that can be accessed by all IPNU cadres, administrators, and members at all levels of management. Based on Action Research Theory, the emergence of SIAPNU and SAM IPNU are IPNU's action in achieving change to be more adaptive to the Industrial Revolution 4.0. IPNU also launched the Penapedia application as a learning management system for IPNU cadres for online education guidance services.